INVESTASI CRYPTOCURRENCY SEBAGAI INSTRUMEN DALAM TRANSAKSI BISNIS - Arka, I Wayan; Indradewi, Anak Agung Sagung Ngurah; Wardani, Luh Ayu Adi (Kerta Dyatmika, 2025)
This research is motivated by the absence of legal norms governing the use of cryptocurrency as an instrument in business transactions. The current legislative framework only regulates licensing, the trading of crypto assets, and the technical provisions for the operation of physical crypto asset markets in futures exchanges. However, it does not specifically address the use of cryptocurrency as a means of conducting business transactions. The objective of this research is to examine and understand the regulation of cryptocurrency as an investment instrument in business transactions and to formulate future regulatory frameworks that may provide legal protection for cryptocurrency users. The method used in this study is normative legal research, employing a statutory and conceptual approach. The findings of the research indicate that cryptocurrency is currently recognized as a commodity that may be traded on futures exchanges under the Commodity Futures Trading Law and further regulated by Bappebti Regulation Number 5 of 2019 concerning Technical Provisions for the Implementation of Physical Crypto Asset Markets in Futures Exchanges. However, this regulation is limited to investment purposes and does not cover the use of cryptocurrency as an instrument in business transactions. In conclusion, future regulation of cryptocurrency should be directed toward providing legal protection for its users in the context of business transactions. This includes legal mechanisms to address user losses, such as the right to void contracts (voidable) and automatic nullification (nietig van rechtswege) in cases of defective consent. Therefore, a comprehensive regulatory framework is needed to ensure the safe and legally secure use of cryptocurrency in business transactions.